Hubungan Karakteristik Individu Terhadap Kepatuhan Penggunaan Alat Pelindung Diri (APD) di PT X - Amalia, Nur; Yuliawati, Ratna; Rachman, Ainur (HIGIENE: Jurnal Kesehatan Lingkungan, 2025)
Personal Protective Equipment (PPE) is a tool used by workers to protect themselves from potential hazards and work accidents that may occur in the workplace. In research, there are still many workers who do not comply with wearing PPE at work because it makes it difficult for them to do their job, starting from not wearing gloves, shoes and eye protection. This researcher aims to determine the relationship between individual characteristics and adherence to the use of PPE personal protective equipment. Quantitative research using a cross sectional approach. Sampling used in this study is the Simple Random Sampling method with workshop workers as respondents totaling 99 using the Slovin formula. Data were collected using a questionnaire and then data were analyzed using SPSS with univariate and bivariate analysis. This data analysis used the chi-square statistical test (α = 0.05). Results: The results showed that the variables age, years of service did not have a significant relationship with adherence to the use of PPE with a p value greater than 0.05, namely the p value of age 0.362 > 0.05 while years of service p value 0.624 > 0.05. There is no relationship between individual characteristics and adherence to the use of personal protective equipment (PPE). Factors that have a relationship with adherence to the use of PPE are age and years of service. Keywords: Compliance, Use of PPE, Workshop